MODEL PEMBELAJARAN ” WEB BASED EDUCATION ” UNTUK MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN KEWARGANEGARAAN DI KELAS XII IPA SMA NEGERI 1 GANTUNG - Sabarudin Sabarudin (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
This study is an action of teachers to improve student learning achievement Civics Class XII Science SMAN 1 Gantung in the Academic Year 2014/2015. This classroom action research conducted in three cycles and includes four phases, namely planning, action, observation and reflection. Each action consists of three activities, namely the preliminary (appersepsi), the core activity of carrying out the Learning Model